KREDIBILITAS GUS DUR SEBAGAI KOMUNIKATOR POLITIK DALAM PROSES DEMOKRATISASI DI INDONESIA - nurkholisoh, nurkholisoh (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2010)
Nahdathul Ulama (NU), Gus Dur and Democratization in Indonesia summarized in this paper. How is the cred ibility of Gus Dur as a statesman of political communication to bring the values of democracy. This qualitative research study will explore more deeply about who Gus Dur is packed with biographical research method, this research makes a reference that should be a reference.